Intracellular Isotope Localization in Ammonia sp. (Foraminifera) of Oxygen-Depleted Environments: Results of Nitrate and Sulfate Labeling Experiments - Nomaki, Hidetaka; Bernhard, Joan M.; Ishida, Akizumi; Tsuchiya, Masashi; Uematsu, Katsuyuki; Tame, Akihiro; Kitahashi, Tomo; Takahata, Naoto; Sano, Yuji; Toyofuku, Takashi (Frontiers in Microbiology, 2016)
Some benthic foraminiferal species are reportedly capable of nitrate storage and denitrification, however, little is known about nitrate incorporation and subsequent utilization of nitrate within their cell. In this study, we investigated where and how much 15N or 34S were assimilated into foraminiferal cells or possible endobionts after incubation with isotopically labeled nitrate and sulfate in dysoxic or anoxic conditions. After two weeks of incubation, foraminiferal specimens were fixed and prepared for Transmission Electron Microscopy (TEM) and correlative nanometer-scale secondary ion mass spectrometry (NanoSIMS) analyses. TEM observations revealed that there were characteristic ultrastructural features typically near the cell periphery in the youngest two or three chambers of the foraminifera exposed to anoxic conditions. These structures, which are electron dense and ~200 to 500 nm in diameter and co-occurred with possible endobionts, were labeled with 15N originated from 15N-labeled nitrate under anoxia and were labeled with both 15N and 34S under dysoxia. The labeling with 15N was more apparent in specimens from the dysoxic incubation, suggesting higher foraminiferal activity or increased availability of the label during exposure to oxygen depletion than to anoxia. Our results suggest that the electron dense bodies in Ammonia sp. play a significant role in nitrate incorporation and/or subsequent nitrogen assimilation during exposure to dysoxic to anoxic conditions.